Experimental investigation of the characteristics of radioactive beams for heavy ion therapy. Issue 7 (11th May 2020) - Chacon, Andrew; James, Benjamin; Tran, Linh; Guatelli, Susanna; Chartier, Lachlan; Prokopvich, Dale; Franklin, Daniel R.; Mohammadi, Akram; Nishikido, Fumihiko; Iwao, Yuma; Akamatsu, Go; Takyu, Sodai; et al.
Abstract : Purpose: This work has two related objectives. The first is to estimate the relative biological effectiveness of two radioactive heavy ion beams based on experimental measurements, and compare these to the relative biological effectiveness of corresponding stable isotopes to determine whether they are therapeutically equivalent. The second aim is to quantitatively compare the quality of images acquired postirradiation using an in‐beam whole‐body positron emission tomography scanner for range verification quality assurance. Methods: The energy deposited by monoenergetic beams of 11 C at 350 MeV/u, 15 O at 250 MeV/u, 12 C at 350 MeV/u, and 16 O at 430 MeV/u was measured using a cruciform transmission ionization chamber in a water phantom at the Heavy Ion Medical Accelerator in Chiba (HIMAC), Japan. Dose‐mean lineal energy was measured at various depths along the path of each beam in a water phantom using a silicon‐on‐insulator mushroom microdosimeter. Using the modified microdosimetric kinetic model, the relative biological effectiveness at 10% survival fraction of the radioactive ion beams was evaluated and compared to that of the corresponding stable ions along the path of the beam. Finally, the postirradiation distributions of positron annihilations resulting from the decay of positron‐emitting nuclei were measured for each beam in a gelatin phantom using the in‐beam whole‐body positron emission tomography scanner at HIMAC. The depth of maximum positron‐annihilation density was compared with the depth of maximum dose deposition and the signal‐to‐background ratios were calculated and compared for images acquired over 5 and 20 min postirradiation of the phantom. Results: In the entrance region, the h b o x RBE 10 was 1.2 ± 0.1 for both 11 C and 12 C beams, while for 15 O and 16 O it was 1.4 ± 0.1 and 1.3 ± 0.1, respectively. At the Bragg peak, the RBE 10 was 2.7 ± 0.4 for 11 C and 2.9 ± 0.4 for 12 C, while for 15 O and 16 O it was 2.7 ± 0.4 and 2.8 ± 0.4, respectively. In the tail region, RBE 10 could only be evaluated for carbon; the RBE 10 was 1.6 ± 0.2 and 1.5 ± 0.1 for 11 C and 12 C, respectively. Positron emission tomography images obtained from gelatin targets irradiated by radioactive ion beams exhibit markedly improved signal‐to‐background ratios compared to those obtained from targets irradiated by nonradioactive ion beams, with 5‐fold and 11‐fold increases in the ratios calculated for the 15 O and 11 C images compared with the values obtained for 16 O and 12 C, respectively. The difference between the depth of maximum dose and the depth of maximum positron annihilation density is 2.4 ± 0.8 mm for 11 C, compared to −5.6 ± 0.8 mm for 12 C and 0.9 ± 0.8 mm for 15 O vs −6.6 ± 0.8 mm for 16 O. Conclusions: The RBE 10 values for 11 C and 15 O were found to be within the 95% confidence interval of the RBEs estimated for their corresponding stable isotopes across each of the regions in which it was evaluated. Furthermore, for a given dose, 11 C and 15 O beams produce much better quality images for range verification compared with 12 C and 16 O, in particular with regard to estimating the location of the Bragg peak. Abstract :